Surgical site infection and associated factors among women underwent cesarean delivery in Debretabor General Hospital, Northwest Ethiopia: hospital based cross sectional study - Mihretu Molla; Kiber Temesgen; Tewodros Seyoum; Mengstu Melkamu (BMC, 2019)
Abstract Background Cesarean section rates have been increasing dramatically during the past three decades and surgical site infections are becoming a leading cause of morbidity and mortality among women undergoing cesarean deliveries. However there is lack of sound evidence on both the magnitude of the problem and the associated factors in developing countries including Ethiopia. The purpose of this study was to assess proportion of surgical site infection and associated factors among women undergoing cesarean delivery in Debretabor General Hospital. Methods An institution based cross sectional study was conducted from May to December / 2017. All women delivered by cesarean section in Debretabor General Hospital during data collection period were our study population. Data were collected using Pre-tested, semi-structured questionnaire/ data extraction tool and post discharge phone follow up and analyzed using SPSS version 20. Logistic regression model was used to determine the association of independent variables with the outcome variable and odds ratios with 95% confidence interval were used to estimate the strength of the association. Results Proportion of surgical site infection among cesarean deliveries was about 8% (95%Cl: 5.4, 11.6). Pregnancy induced hypertension (AOR = 4.75, 95%CI: 1.62, 13.92), chorioaminitis (AOR = 4.37, 95%CI: 1.53, 12.50), midline skin incision (AOR = 5.19, 95% CI: 1.87, 14.37 and post-operative hemoglobin less than 11 g/deciliter (AOR = 5.28, 95%CI: 1.97, 14.18) were significantly associated with surgical site infection. Conclusions Pregnancy induced hypertension, chorioaminitis, midline skin incision and post-operative hemoglobin of less than 11 g/deciliter were independent factors associated with surgical site infection. Cesarean deliveries with concomitant pregnancy induced hypertension, chorioaminitis and post-operative anemia needs special care and follow up until surgical site infection is ruled out. It is also advisable to reduce generous midline skin incision and better replaced with pfannensteil incision.